The Effect of Interactive Performance Measurement System and Participatory Budgeting on Job Challenge and Their Impact on Managerial Performance - Aditya, Fadly; Dahlan, Muhammad; Hasyir, Dede Abdul (Budapest International Research and Critics University, 2021)
This research was conducted on State-Owned Enterprises in Indonesia. This study aims to determine the relationship between interactive performance measurement systems, participatory budgeting and managerial performance, as well as how the role of job challenges on other variables. By using primary data. Purposive sampling is used to determine the sample. The sample used in this study was 37 middle-level managers in SOEs in Indonesian. The analytical method used is the partial least squares structural equation modeling (PLS-SEM) method with SmartPLS. The results showed that the interactive performance measurement system and participatory budgeting had a significant positive effect on managerial performance either directly or indirectly mediated by job challenges.